Time With Peers From Middle Childhood to Late Adolescence: Developmental Course and Adjustment Correlates. Issue 4 (22nd February 2014) - Lam, Chun Bun; McHale, Susan M.; Crouter, Ann C.
<x xml:space="preserve">Abstract</x> This study examined the developmental course and adjustment correlates of time with peers from age 8 to 18. On seven occasions over 8 years, the two eldest siblings from 201 European American, working‐ and middle‐class families provided questionnaire and/or phone diary data. Multilevel models revealed that girls' time with mixed‐/opposite‐sex peers increased beginning in middle childhood, but boys' time increased beginning in early adolescence. For both girls and boys, time with same‐sex peers peaked in middle adolescence. At the within‐person level, unsupervised time with mixed‐/opposite‐sex peers longitudinally predicted problem behaviors and depressive symptoms, and supervised time with mixed‐/opposite‐sex peers longitudinally predicted better school performance. Findings highlight the importance of social context in understanding peer involvement and its implications for youth development.